Crime and Control at the Chess Park - Bonomo, Elizabeth A. (2016)
This dissertation is an ethnographic study of a public chess park located in the heart of downtown Atlanta. The chess park brings together persons from all backgrounds, although most are African American, poor (often homeless), unemployed, and male. The chess park is nestled among office buildings, college classrooms, various shops and restaurants, and, perhaps not coincidentally, directly across from a police precinct. Despite this visibility, however, the chess players regularly engage in public illicit behavior. This includes, but not limited to, a pervasive and wholly self-regulated underground economy, illicit drug use, and public drinking. Drawing on extensive field observations and interviews, this study examines why the chess players go to the park, how they avoid formal sanction when committing prohibited acts, and, when that fails, how they are sanctioned and to what effect. The chess players go to the park to play chess, for its central location, for community, and to hustle and engage in vice. When engaged in the latter, they try to prevent sanction through passing as normal by playing chess, using props, using blockades, being on the lookout, and showing respect. Such measures are not always executed or successful, though. Thus, sometimes the chess players are caught violating a prohibition by ambassadors or police officers. These authority figures handle such acts by giving warnings, asking the individual to leave, and making an arrest. Though these sanctions deter misbehavior in the short-term, they appear to have no long-term effect. The dissertation concludes by discussing how the findings inform larger debates in criminology and criminal justice